Islamic Values and Digital Media Ethics in Santri-Family Communication in the Digital Era - Susri Adeni; Machyudin Agung Harahap (INJECT (Interdisciplinary Journal of Communication), 2025)
This study explores how parents of Islamic boarding school students (santri) communicate and instill ethical values in their children's digital media use. Utilizing a qualitative narrative approach with 22 parent informants from PPQ Nahwa Nur, the research uncovers various parental communication patterns, Islamic values, challenges, and strategies in navigating digital parenting. The findings show a blend of restrictive and active mediation, rooted in Islamic teachings and dialogic approaches. Challenges include peer influence, digital addiction, and parental digital illiteracy. This study contributes to understanding family communication in religious boarding school contexts and suggests pathways for Islamic-based digital literacy programs.